Analysis of student achievements using ordered logistic regression - Murauskas, Gediminas; Radavičius, Marijus (Lietuvos matematikos rinkinys, 2010)
In the paper the problem of assessment of mathematical abilities is addressed. It is assumed that student’s grade in the mathematical analysis is one of the main indices of mathematical abilities which gives rather reliable guess of his further academic performance in mathematics. Relationships of the mathematical analysis grades with other factors including the examinator’s effect are investigated using data of Vilnius University students in mathematics and rank logistic regression with a variable scale.
Keywords: achievement analysis; interactions; mathematical abilities; ordered logistic regression; proportional odds